Neuroscience and Behavioral Physiology - Balaban, Pavel M.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
Neuroscience and Behavioral Physiology contains translations of papers selected from top Russian journals describing significant results of studies on the nervous system. Priority is given to new experimental findings. Neuroscience and Behavioral Physiology publishes contributions of international importance in the fields of physiology, psychopharmacology, neuroendocrinology and neurochemistry, as well as in the anatomy and pathology of the nervous system. Special attention is given to research relating brain function with behavior. Reviews are also provided of the current status of entire fields of Russian research.
Keywords: Neurosciences; Behavioral sciences; Neurobiology; Neurosciences; Neurobiology; Behavioral Sciences